1982
DOI: 10.1152/ajpregu.1982.243.3.r400
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of blood-brain barrier permeability to, and cerebrospinal fluid sink action on, [14C]urea

Abstract: To ascertain the ontogeny of CSF sink action on a small hydrophilic solute, we investigated the rate and extent of uptake of [14C]urea by lateral ventricle choroid plexus (CP), cisternal cerebrospinal fluid (CSF), cerebral cortex, and cerebellum in 0.5- to 4-wk-old etherized nephrectomized rats. Five hours after ip injection, radiourea penetrated the entire H2O of tissue and CSF in 1-wk-old brain; moreover, for animals 1-4 wk old there was a marked inverse relationship between age and magnitude of steady-state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 0 publications
3
21
0
Order By: Relevance
“…Analysis of lithium concentration in the PVWM by atomic absorption demonstrated that injected agents are diluted 20-to 30-fold following intraventricular injection. This is due to the direct dilution of the injectate in the volume of the CSF and the rapid turnover of CSF and drainage into the subarachnoid spaces, and our findings are entirely consistent with measurements of a range of small and large molecular weight agents (Nagaraja et al, 2005;Parandoosh and Johanson, 1982). We tested diverse GSK3b inhibitors and they all had equivalent effects, increasing OPs and OLs and promoting myelination in the PVWM.…”
Section: Gsk3b Inhibitors Injected Into the Lateral Ventricle Affect Olssupporting
confidence: 87%
“…Analysis of lithium concentration in the PVWM by atomic absorption demonstrated that injected agents are diluted 20-to 30-fold following intraventricular injection. This is due to the direct dilution of the injectate in the volume of the CSF and the rapid turnover of CSF and drainage into the subarachnoid spaces, and our findings are entirely consistent with measurements of a range of small and large molecular weight agents (Nagaraja et al, 2005;Parandoosh and Johanson, 1982). We tested diverse GSK3b inhibitors and they all had equivalent effects, increasing OPs and OLs and promoting myelination in the PVWM.…”
Section: Gsk3b Inhibitors Injected Into the Lateral Ventricle Affect Olssupporting
confidence: 87%
“…Two examples are the translocation of water and amyloid peptides by aquaporins (3) and the LRP-1 transporter (3,40), respectively. Conceptualizing both plasma and CSF as potential sinks (40,44) on water and solutes will enhance pharmacotherapy to ameliorate hydrocephalus and Alzheimer's disease (3,41).…”
Section: New Outlooks For Csf Translational Research and Therapymentioning
confidence: 99%
“…A worthy goal is to identify agents that stabilize the BCSFB and allow CP to maintain CSF formation in senescence. This would maintain CSF sink action (44) and the clearance of harmful toxins (3,41,43). Otherwise, stagnated CSF dynamics in advanced aging predisposes to the dementia of chronic hydrocephalus (41).…”
Section: New Outlooks For Csf Translational Research and Therapymentioning
confidence: 99%
“…Consequently, there is paracellular diffusion of small hydrophilic solutes through CP tight junctions and onward into CSF. For example, intravascularly administered mannitol (M W = 182) and inulin polysaccharide (M W õ 5,500) penetrate into CSF (16,17) by diffusing between choroid epithelial cells rather than through them (18,19).…”
Section: Epithelial Tight Junctions and Paracellular Diffusionmentioning
confidence: 99%